Peran Modal Sosial dalam Upaya Eliminasi Tuberkulosis Berbasis Komunitas (Studi Kasus Mentari Sehat Indonesia Kota Semarang) - Ghisya Sauqina Rosyada; Kuncoro Bayu Prasetyo (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Tuberculosis (TB) remains a serious public health problem in Indonesia. Although the government has implemented various policy strategies and expanded access to healthcare services, TB case numbers have not shown a significant decline. This condition highlights the importance of community participation through a community-based approach. This study aims to analyze the role of social capital in community-based TB elimination efforts conducted by Mentari Sehat Indonesia (MSI) in Semarang City. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with MSI administrators, cadres, and beneficiary patients, as well as through participatory field observations. The analysis applies Robert D. Putnam’s theory of social capital, which emphasizes three main dimensions: social networks, trust, and social norms. The findings reveal that MSI reproduces and strengthens social capital that has been built since its earlier affiliation with the ‘Aisyiyah organization. Social networks have been expanded through partnerships with donor agencies, local governments, and philanthropic institutions such as the Bakrie Center Foundation. Trust serves as a key element connecting MSI with its cadres and linking cadres with patients through empathetic mentoring, open communication, and consistent support during the treatment process. Meanwhile, social norms such as reciprocity, mutual assistance, pluralism, and kinship strengthen the program’s sustainability. This social capital significantly contributes to the effectiveness and continuity of the community-based TB elimination program.